Geomorphological analysis of landform in Jonk river basin, Eastern India: A geospatial approach - Km.Shiwani; Roohi Rawat (National Geographical Journal of India, 2023)
Basin geomorphology typically involves the study of landforms of the basin. Geomorphology controls the movement of water in the basin. Quantitative interpretation of the geomorphology of a basin is significant to understand the surface run-off behaviour and to analyse the basin issues like soil erosion which will be helpful for the prediction of water retention function and making prevention and conservation strategies to stimulate water infiltration. The study focuses on analysing the complex geology, gradient behaviour, and characteristics of different geomorphic units of the Jonk river basin with geospatial techniques. ALOS PALSAR DEM is used for slope and relief analysis, and preparation of the Topographic Position Index (TPI). The slope direction is from south to northeast. The pediment-peneplain complex is the most extensive geomorphic unit observed in the basin, covering 72.79% of the basin. Anthropogenic terrain with 0.24% of the basin’s surface is the smallest geomorphological unit of the basin. TPI gives a clear understanding of the hills and valleys configuration of the southern and northern highlands of the Jonk river basin.